Asymmetric Iterative Hydration of Polyene Strategy to Cryptocaryols A and B - Hunter, Thomas J.; Wang, Yanping; Zheng, Jiamin; O’Doherty, George A. (Synthesis, 2016)
The development of two iterative asymmetric hydration approaches to the synthesis of all syn- and syn/anti/syn-1,3,5,7-tetraol motifs is described. These pseudo-symmetric products are synthetic precursors for 1,3-hexol products. The utility of the route to the all syn-1,3,5,7-tetraol diastereoisomer was demonstrated with its use in the synthesis of cryptocaryols A and B, as well as, stereoisomers.
Keywords: asymmetric synthesis; iterative hydration; cryptocaryol A; cryptocaryol B; 1,3-polyols